Akuntansi Manajemen Strategik Pada Koperasi (Strategic Management Accounting In Cooperatives) - Susilawati, Made (STIE Malangkucecwara, 2022)
The purpose of this study is to examine how important strategic management accounting is in advancing cooperatives. This study uses a qualitative method through a case study approach. Data were collected through interviews, observation, and literature study. The object of the research is the application of strategic management accounting in cooperatives. The findings of this study are management accounting strategies contribute to advancing cooperatives, but there are still few cooperatives that apply strategic management accounting strategies due to constraints on understanding the roles and functions of cooperative elements, recruiting members and selecting cooperative management, capital, systems and technology, and commitment. These obstacles can be overcome by implementing strategic management accounting which stimulates to collect information, analyze, interpret, recommend solution strategies, and communicate to cooperative management so that they can be used as considerations related to decision making in planning, controlling, evaluating, and continual improvement.